Can People Recollect Well and Change Their Source Memory Bias of "Aha!" Experiences?. (7th April 2015) - Du, Xiumin; Zhang, Ke; Wang, Jiali; Luo, Junlong; Luo, Jing
Abstract: Although many scientific discoveries were frequently reported as kinds of insightful breakthrough that suddenly illuminated in one's mind, we can never exactly know whether these afterward reports were reliable or not. In this study, subjects were asked to solve a list of Remote Associate Test problems and got both subsets of the insightfully and routinely solved items. Then, this study examined whether people can recollect their "Aha!" experiences as well as "non‐Aha" ones. It was found that subjects were more accurate in recollecting their Aha! experiences relative to the routine ones. The study further examined if the report bias of Aha! or non‐Aha problem solving experiences could be changed by the afterward‐suggestive information that indicated the discovery is unique (rare) or not. It was found that the tendency for participants to falsely recollect their routine problem solving experience as Aha! ones if they were told the item they had solved was very rare, and the tendency to falsely recollect the Aha! problem solving experiences as routine ones if the item were said to be common.